2019
DOI: 10.5937/kgjsci1941159b
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation, translocation and phytoremediation by endemic serpentinophyte Artemisia alba Turra

Abstract: The aim of this study was to determine the concentrations of some metals (Ca, Mg, Fe, Mn, Zn, Ni, Cr) in the soil and in the endemic serpentinophyte Artemisia alba Turra. (Artemisia lobelii All.) on one serpentine site (Central Serbia), for determination the ability of this plant species in bioaccumulation, translocation and phytoremediation of researched metals. The concentrations of Ni and Cr in the investigated soil were above remediation values, the maximum allowable concentration, as well as of prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some studies indicated the ability of different species belonging to Artemisia genus to accumulate heavy metals e.g. ( Alirzayeva et al, 2006 , Rebhi et al, 2019 , Kumari et al, 2018 , Branković et al, 2019 ). Similarly, some studies indicated the ability of R .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated the ability of different species belonging to Artemisia genus to accumulate heavy metals e.g. ( Alirzayeva et al, 2006 , Rebhi et al, 2019 , Kumari et al, 2018 , Branković et al, 2019 ). Similarly, some studies indicated the ability of R .…”
Section: Discussionmentioning
confidence: 99%
“…It includes around 500 species including perennial herbs and shrubs which were historically used in pharmaceutical and cosmetic preparations [ 12 ], thanks to their high content of active compounds such as essential oils, tannins, organic acids, carotenoids, ascorbic acid, and glycosides [ 13 ] with antioxidant, antiviral, and bactericidal activity [ 14 , 15 ]. A. absinthium has already been successfully used for salt- and heavy metal- phytoremediation [ 16 , 17 , 18 , 19 ]. Artemisia spp.…”
Section: Introductionmentioning
confidence: 99%